(untitled) (The University of Nairobi Journal of Language and Linguistics, 2023)
On the underlying assumption that the student should be at the centre of the learning process, this paper attempts an overview of different types of needs that students may have when learning a foreign language. It also touches briefly on the setting of behavioural objectives, and the importance of language awareness and learner’s autonomy in the learning process.